تأثير التغطية الشجرية في خصائص الغطاء العشبي لغابة ضهر الخريبات (جبلة – اللاذقية) - شيخ محمد, ياسين; جمعة, نور (Latakia University Journal -Biological Sciences Series, 2019)
The research had been implemented in Daher Al Kheribat forest in Jableh area in Syria in 2014 -2019 with aim to know how the tree cover affects the characters of the herbal plants in the area. Three different tree cover sites were selected: the first 80%, the second 60%, the third 30%, tree cover estimated by naked eye. Modified ACSAD method had been adopted to estimate the plant coverage and relative coverage, and square method to estimate the intensity and frequency, There were 58 plant species on the whole site belonging to 48 genuses distributed in 21 families, the most families appearance was Poaceae. The highest value of the species richness (27) and relative abundance (3.54) obtained in the third site. The relative importance of the first site was 4.01%, in the second 3.06%, and in the third 2.32%. The following species Bromus tectorum L., Alopecurus urticulatus Banks & Sol., Aegilops ventricosa Taush., Polycarpon tetraphyllum L., Bromus squarrosus L. obtained the highest values of relative importance in the three sites and the highest value obtained in the second site (29.89 ، 16.65 ، 5.33 ، 3.72 ، 3.46 in order). The proportions of vegetative similarity were not affected by the density of the tree cover. نُفِّذَ هذا البحث في غابة ضهر الخريبات بمنطقة جبلة في سورية خلال الفترة 2014- 2019 بهدف معرفة تأثير التغطية الشجرية في خصائص الغطاء النباتي العشبي لطبقة تحت الغابة. اختيرت ثلاثة مواقع مختلفة التغطية الشجرية: الأول 80%، الثاني 60%، الثالث 30%، وقُدِّرَت التغطية الشجرية بالعين المجردة. اعتُمِدَت طريقة أكساد المعدَّلة لقياس التغطية العشبية، وطريقة المربعات لقياس التردد والكثافة. سجِّل وجود 58 نوعاً نباتياً في منطقة الدراسة, تنتمي لفصائل نباتية مختلفة (21 فصيلة)، ونباتات الفصيلة الكلئية Poaceae هي الأكثر ظهوراً. أبدى الموقع الثالث أعلى قيمة للغنى النوعي (27)، والوفرة النسبية (3.54). بلغ متوسط الأهمية النسبية في الموقع الأول %4.01، وفي الثاني%3.06 ، وفي الثالث %2.32 وقد حصلت الأنواع:Bromus tectorum L., Alopecurus urticulatus Banks & Sol., squarrosus L., Polycarpon tetraphyllum L., Aegilops ventricosa Taush.. B. على القيم الأعلى للأهمية النسبية في المواقع الثلاثة، واحتل الموقع الثاني أعلى أهمية نسبية لتلك الأنواع (29.89 ، 16.65 ، 5.33 ، 3.72 ، 3.46 بالترتيب). ولم تتأثر نسب التشابه النبتي في المواقع الثلاثة بكثافة الغطاء الشجري.